Clickable Radiocomplexes With Trivalent Radiometals for Cancer Theranostics: In vitro and in vivo Studies - D'Onofrio, Alice; Silva, Francisco; Gano, Lurdes; Karczmarczyk, Urszula; Mikołajczak, Renata; Garnuszek, Piotr; Paulo, António (Frontiers in Medicine, 2021)
Pre-targeting approaches based on the inverse-electron-demand Diels-Alder (iEDDA) reaction between strained trans-cyclooctenes (TCO) and electron-deficient tetrazines (Tz) have emerged in recent years as valid alternatives to classic targeted strategies to improve the diagnostic and therapeutic properties of radioactive probes. To explore these pre-targeting strategies based on in vivo click chemistry, a small family of clickable chelators was synthesized and radiolabelled with medically relevant trivalent radiometals. The structure of the clickable chelators was diversified to modulate the pharmacokinetics of the resulting [111In]In-radiocomplexes, as assessed upon injection in healthy mice. The derivative DOTA-Tz was chosen to pursue the studies upon radiolabelling with 90Y, yielding a radiocomplex with high specific activity, high radiochemical yields and suitable in vitro stability. The [90Y]Y-DOTA-Tz complex was evaluated in a prostate cancer PC3 xenograft by ex-vivo biodistribution studies and Cerenkov luminescence imaging (CLI). The results highlighted a quick elimination through the renal system and no relevant accumulation in non-target organs or non-specific tumor uptake. Furthermore, a clickable bombesin antagonist was injected in PC3 tumor-bearing mice followed by the radiocomplex [90Y]Y-DOTA-Tz, and the mice imaged by CLI at different post-injection times (p.i.). Analysis of the images 15 min and 1 h p.i. pointed out an encouraging quick tumor uptake with a fast washout, providing a preliminary proof of concept of the usefulness of the designed clickable complexes for pre-targeting strategies. To the best of our knowledge, the use of peptide antagonists for this purpose was not explored before. Further investigations are needed to optimize the pre-targeting approach based on this type of biomolecules and evaluate its eventual advantages.